2021
DOI: 10.1186/s13018-021-02589-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for screw loosening in patients with adult degenerative scoliosis: the importance of paraspinal muscle degeneration

Abstract: Background Paraspinal muscle is an important component to maintain spinal stability. But the relationship between the degeneration of paraspinal muscle and postoperative screw loosening in patients with adult degenerative scoliosis has not been studied. The objective of this study was to investigate risk factors for screw loosening in patients with adult degenerative scoliosis, including paraspinal muscle degeneration. Methods We investigated 93 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Alterations in muscle structure and function, especially fatty infiltration and fibrosis, are clearly associated with spinal disorders [36]. An increasing number of studies have shown that in patients with DKS, the cross-sectional area of the lumbar erector spinae and psoas major is significantly thinner, and pathological assessment shows muscle atrophy, necrosis, and hyaline fibrosis, while muscle fat infiltration and inflammatory cell infiltration are more pronounced [37][38][39]. Therefore, we also performed pathological examination of the paraspinal muscle tissue of DKS mice by HE staining and Masson staining.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in muscle structure and function, especially fatty infiltration and fibrosis, are clearly associated with spinal disorders [36]. An increasing number of studies have shown that in patients with DKS, the cross-sectional area of the lumbar erector spinae and psoas major is significantly thinner, and pathological assessment shows muscle atrophy, necrosis, and hyaline fibrosis, while muscle fat infiltration and inflammatory cell infiltration are more pronounced [37][38][39]. Therefore, we also performed pathological examination of the paraspinal muscle tissue of DKS mice by HE staining and Masson staining.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported lower preoperative thoracolumbar muscle quality in patients with proximal junctional kyphosis (PJK) and even muscle degeneration as a risk factor for occurrence of PJK (39)(40)(41). Furthermore, several studies reported that poor muscle quality is correlated with distal screw loosening in patients with DS after corrective surgery (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because, in predisposed subjects, from the biomechanical point of view, the pushing force of the paravertebral muscles is lost, which is essential to counteract the establishment and evolution of the scoliotic curve [ 26 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 34 , 35 , 45 ] have hypothesized that the relationship between low body mass index and scoliosis may be a consequence of hormonal problems [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%